Assessment of biochemical, cooking, sensory and textural properties of the boiled food product of white yam (D. rotundata) genotypes grown at different locations - Alamu, Emmanuel Oladeji; Adesokan, Michael; Awoyale, W.; Oyedele, H.A.; Fawole, S.; Amele, A.; Maziya-Dixon, Busie (Elsevier, 2022)
Specific biochemical properties and textural attributes determine the final quality and acceptability of yam food products. This study assessed the flour and cooking qualities (boiled yam) of sixteen elite white yam genotypes (D. rotundata) grown in three locations. Fresh yam samples were cut into regular-shaped pieces and boiled using the standard procedure. Sub-samples were oven-dried at 65 °C for 72 h and milled to flour. The biochemical profiling for the yam flour showed, on average, 61.35 ± 5.15% starch, 5.35 ± 0.15% sugar, 1.55 ± 0.24% crude fiber, 1.91 ± 0.31% ash, 5.65 ± 0.66% protein, 0.33 ± 0.02% fat and 34.87 ± 1.94% amylose content. The boiled yam's water absorption and cooking time ranged from 0.35 to 5.17% and 7.00–18 min, with an average of 2.74% and 10.64 min, respectively. The hardness of boiled yam from the sensory assay correlated positively with the hardness of instrumental texture analysis (p<0.001, r=0.47). In contrast, the hardness of instrumental texture had a significant negative correlation with the chewiness of sensory profile analysis (p < 0.05, r = 0.37). Likewise, water absorption correlated positively and significantly (p<0.05, r=0.43) with the chewiness of the sensory analysis. The study shows that the sensory attributes that determine the acceptability of boiled yam could be determined using instrumental measurements to save time and cost.